Report on community diagnosis to reduce the number of new malnutrition cases in the toddlers - Margaretha Pramesthi Utari; Ella Windasari Gultom; Tamara Muliani; Silviana Tirtasari (Science Midwifery, 2023)
Community diagnosis can be used to determine problems in the community, including analyzing the situation, identifying, prioritizing, and solving the problem. According to WHO, in 2017, 50% of child and infant mortality was caused by malnutrition. More than two-thirds of all children have malnutrition, especially severely wasting in Asia. Indonesia is the second country with the highest severe wasting rate in toddlers (2017 - 2021). Riskesdas 2018 shows that 3,5% of toddlers in Indonesia are severely wasted. The prevalence of wasted toddlers in Tangerang Regency 2021 is the highest compared to other districts in Banten. Data from the Cikupa Health Center showed an increase in new cases of severe wasting in toddlers between 2021 and January-June 2022. This research aims to recognize the location with the highest new case of severe wasting in toddlers that must be intervened immediately, the problems, interventions, and its results. Method community diagnosis has been used to overcome health issues in Cikupa Public Health Center. After the intervention, it showed 26 mothers with toddlers obtained a post-test score of> 80, 2 mothers with toddlers could mention a nutritious and varied food menu in one day for toddlers, and it was also found that eight toddlers with severe wasting. Talaga is the main location for the increase in new cases of severe wasting in toddlers caused by lifestyle. Interventions, such as counseling, demonstrations, and screenings, are expected to reduce new cases of severe wasting in toddlers at Cikupa Public Health Center